2008
DOI: 10.1186/1752-2897-2-9
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell transfusion within the first 24 hours of admission is associated with increased mortality in the pediatric trauma population: a retrospective cohort study

Abstract: Background: Allogeneic red blood cell transfusion is associated with increased morbidity and mortality in adult trauma patients. Although studies have suggested that the adoption of a more restrictive transfusion strategy may be safely applied to critically ill adult and all-cause critically ill pediatric patients, recent developments in our understanding of the negative consequences of red blood cell transfusion have focused almost entirely on adult populations, while the applicability of these findings to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Elevated SI has also been shown to predict mortality [2,6,10,11] and need for critical care [10,[12][13][14][15][16] in adults. Studies in children have conflicting results with trauma studies showing an SI predictive of hemorrhagic shock [17] and a composite measure of trauma outcomes [18] with a few SI studies finding no predictive value [19][20][21].…”
Section: Introductionmentioning
confidence: 98%
“…Elevated SI has also been shown to predict mortality [2,6,10,11] and need for critical care [10,[12][13][14][15][16] in adults. Studies in children have conflicting results with trauma studies showing an SI predictive of hemorrhagic shock [17] and a composite measure of trauma outcomes [18] with a few SI studies finding no predictive value [19][20][21].…”
Section: Introductionmentioning
confidence: 98%
“…This increases the likelihood of trauma patients getting older PRBCs as they may require multiple transfusions. In recent years, studies have examined the issue of RBC unit length of storage and its effects on adult trauma patients (8)(9)(10)(11). Spinella et al (8) in 2009 reported poorer outcomes associated with the transfusion of PRBCs older than 28 days in adult trauma patients.…”
mentioning
confidence: 98%
“…Stone et al 39 found an association with increased mortality in pediatric trauma patients who received transfusion within 24 hours of admission. Demaret et al 40 studied the effect of blood transfusions in critically ill children.…”
Section: Blood Transfusion In Other Specialtiesmentioning
confidence: 99%